2000
DOI: 10.1302/0301-620x.82b8.0821189
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral movement 1: the shapes and relative movements of the femur and tibia in the unloaded cadaver knee

Abstract: In six unloaded cadaver knees we used MRI to determine the shapes of the articular surfaces and their relative movements. These were confirmed by dissection.Medially, the femoral condyle in sagittal section is composed of the arcs of two circles and that of the tibia of two angled flats. The anterior facets articulate in extension. At about 20° the femur 'rocks' to articulate through the posterior facets. The medial femoral condyle does not move anteroposteriorly with flexion to 110°.Laterally, the femoral con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
335
6
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(375 citation statements)
references
References 4 publications
(7 reference statements)
23
335
6
1
Order By: Relevance
“…From 208 to 808 flexion the contact locations moved posterior, inclined 158 to 208 with respect to the tibia, maintaining the femur approximately in line with the foot as previously reported. 11 However, unlike previous reports, contact-derived rotation continued from 808 to full flexion in squat and kneel. From 808 to maximum flexion, the contact-derived and rigid body bone rotations showed similar curves, which is reasonable considering the circular geometry of the posterior femoral condyles.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…From 208 to 808 flexion the contact locations moved posterior, inclined 158 to 208 with respect to the tibia, maintaining the femur approximately in line with the foot as previously reported. 11 However, unlike previous reports, contact-derived rotation continued from 808 to full flexion in squat and kneel. From 808 to maximum flexion, the contact-derived and rigid body bone rotations showed similar curves, which is reasonable considering the circular geometry of the posterior femoral condyles.…”
Section: Discussioncontrasting
confidence: 62%
“…Significant differences in early flexion (08 to 308) are due to femoral geometry. Iwaki et al 11 showed that the sagittal profile of the medial femoral condyle is composed of a larger distal and smaller posterior circular arc, while the lateral condyle is well described by a single circular facet. From extension to mid flexion, the medial tibial contact area had a more ovoid shape and moved posteriorly (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported with findings from fluoroscopy, studies using in vitro analyses, and those using external markers associated with gait laboratory systems [1, 2, 4, 8-10, 12, 13, 16, 18, 19, 21, 22, 24, 25, 34-37]. With increasing knee flexion, the normal knee reportedly experiences more posterior motion of the lateral condyle leading to internal rotation of the tibia with respect to the femur [18,22,25]. In contrast to the normal knee, in vivo kinematic analyses suggest subjects undergoing TKA often experience a motion pattern opposite the normal knee where the condyles slide in the anterior direction with increasing knee flexion [2,8,9,24,28,31,[34][35][36][37].…”
Section: Introductionsupporting
confidence: 67%
“…Although morphological studies on the shape and congruence of the tibia and femur have been conducted (Iwaki et al, 2000), the nature of tibial rotation in normal subjects is not well understood, with many researchers having used measurements obtained at close to terminal extension to see if the tibia rotates externally with knee extension, an effect known as screw-home motion (Hallen & Lindahl, 1966;Todo et al, 1999;Iwaki et al, 2000;Piazza & …”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have been conducted to determine tibial displacement on the femur at different knee angles of flexion (Iwaki et al, 2000;Logan et al, 2004), the degree of in vivo tibial rotation at different angles remains relatively undetermined.…”
Section: Introductionmentioning
confidence: 99%